Lactoferrin gene polymorphisms in Italian patients with recurrent tonsillitis. - Zupin, Luisa; Angelelli, Francesco; Grasso, Domenico Leonardo; Crovella, Sergio (Int J Pediatr Otorhinolaryngol, 2016)
INTRODUCTION: Recurrent tonsillitis is an oral pathology characterized by inflammation of tonsils. The disease susceptibility depends upon environmental and host factors, specifically the innate immune response, the first line of host defence could play an important role. Among innate immunity members, lactoferrin, known for its antimicrobial properties, was previously correlated with the risk of oral pathology as periodontitis and dental caries. METHODS: 89 Italian children presenting recurrent tonsillitis and 95 healthy children were genotyped for two LTF non-synonymous polymorphisms, called Thr29Ala and Arg47Lys, in order to investigate their potential role in recurrent tonsillitis susceptibility. RESULTS: no different allele, genotype and haplotype frequency distributions were detected comparing patients and controls. CONCLUSION: data from the current study indicate that LTF polymorphisms might not be involved in recurrent tonsillitis development in our Italian population. However, since the importance of lactoferrin in oral immunity has been previously assessed, further studies should be necessary to unravel the potential role of LTF genetic variants in oral cavity.